HEALTH EQUITY AND WOMEN’S PARTICIPATION - Mary, fmm, Dr. Sr. Lourthu (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
This paper examines the social and theoretical underpinning of women’s participation in health equity and safety. Despite various policies and legal entitlements health inequities have been persistence at a national and global level. Women’s risk factors associated with age, geographical domain, political turbulence and with a different section of groups namely childhood, adolescence, pregnancy, elderly, working, urban, rural, etc. Health equity as human rights, need women’s active participation to accelerate development. The theory of Education/participation by Freire (1968) provides social strategies and psychological understanding of the oppressed mass to induce a change in the larger systems. The theories directed to the social system’s objectives and all its components with practical orientation kindle functionalities that are precise and clearer. Based on the education theory four levels of participation have been examined to study women’s participation for health equity at Perambakkam (South Chennai) displaced community. The health assumption has been examined with the support of empirical evidence to justify the incidence of health inequity in the community which is a matter of concern. The analysis suggests twelve principles of participation of women to demand health equity. The finding suggest that effective participation is one that is initiated from below, voluntary, organized, direct, continuous, and broad in scope and empowered. Indirect participation may be quite appropriate and satisfactory in some situations. Ideal performance is the result of ideal conditions. Although advocacy for participation waxes and wanes, in today’s context it has been recognized as the most important governance principle for change in health equity.